Analiza kulturowo-cywilizacyjna publicznego dyskursu łamania prawa w Rosji i na Ukrainie: Cultural and civilization analysis of public discourses of lawbreaking in Russia and Ukraine - Leszczak, Oleg; Prosianyk, Oksana (Przegląd Wschodnioeuropejski, 2021)
The paper focuses on the notion of legal culture in anthropocentric depiction as an informational-semiotic function. The authors present a typology of cultural-civilisational motives for breaking the law. A range of cultural-civilisational motives (naturalistic, turanic, byzantinic, theocratic, europeistic, and consumerist) expressed in the form of discursive statements was presented in detail; these motives cause breaking the law in a causal synergetic mode (ignorance of the law) and in a cybernetic mode (disregard for the law). The authors distinguish several types of verbal excuses for breaking the law widespread in Russian and Ukrainian legal culture discourse.